Pengembangan Sistem Smart Village Berbasis Internet of Things untuk Meningkatkan Kualitas Hidup di Desa - Harun Sujadi; Nunu Nurdiana; Reyna Indra Maulana (Indonesian Society of Applied Science, 2023)
Internet users in Indonesia reached 55% or more than half of Indonesia's population, while the tools used to access the internet are dominated by smartphones, as much as 60%. These make the internet and smartphones one of the technologies that can be used further. Internet of Things is one of the technological developments in the internet field that can be used in building smart villages. A smart village is an innovative village that seeks to improve its citizens' quality of life, efficiency, and competitiveness by utilizing information and communication technology (ICT). Simdesapp is an intelligent village application that was built to display information obtained from the previously built smartpole hardware—using the Extreme Programming method as a system development method through several stages such as planning, design, coding and testing. The features contained in the software are monitoring temperature, humidity, air quality, panic buttons for emergencies, and early warnings for disasters such as land fires and earthquakes. In contrast, other features in the software are the history of each resident's illness, schedule Posyandu, patrol schedules, profiles of each resident, and village website containing profiles and village potentials.